Sub-regional perspectives on structural change - Pedro M. G. Martins (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2015)
This paper provides a comprehensive assessment of structural change patterns in the world economy. It uses a new dataset on sectoral employment produced by the International Labour Organization, which is complemented by national accounts and population data from the United Nations Department of Economic and Social Affairs. The sample includes 169 countries, representing about 99 percent of the world's output and population in 2013. One of the main contributions of this paper is its focus on the sub-regional level, which has been hitherto absent from the literature. We provide an assessment of 13 sub-regions in Africa, Asia and Latin America in order to offer deeper and richer insights into the recent dynamics of structural change. Overall, our results suggest that within-sector productivity improvements were the key driver of output per capita growth in most sub-regions. Nonetheless, structural change has also played a critical role in enhancing economic performance since 2002 - mainly through services. Changes in the demographic structure and employment rates have also contributed to the recent performance, albeit to a much lesser extent. Accelerating the pace of structural change - by exploiting existing productivity gaps - will be crucial to sustain current economic growth rates in developing regions.
Keywords: J20; O11; O40; 330; structural change; labour productivity